PROTEIN EXCHANGE IN THE BODY OF PIGS FOR USE VITAMIN E AND CITRATES OF MICROELEMENTS - Tokarchuk, T.S.; Antonetska, L.V.; Kolashchuk , L.H. (Podilian Bulletin: Agriculture, Engineering, Economics, 2020)
The main reasons for the death of young animals and their growth retardation are various nutritional diseases, among which the most common in suckling piglets are ferum-deficient anemia, as well as stress factors caused by technological processes. Therefore, mineral elements must always enter the animals’ body with food or water and normalize metabolism and energy exchange, ensure the enzymes and hormones work. After weaning of piglets and the use of poor-quality compound feed-pre-starter during this period against the stress background, a high percentage of their death is observed. To increase the resistance, survival and suckling pigs productivity and piglets after weaning, it is effective to use vitamin and mineral agents, including the micellar form of vitamin E and citrates of trace elements. Evaluating vitamin and mineral preparations, it is advisable to study the parameters of protein metabolism in the blood serum of young pigs. Protein plays a leading role in metabolism. This is an irreplaceable material that participates in the nutrition process, the new cells formation, the regeneration of individual cellular structures, in the formation of nonspecific defense of the body, the synthesis of enzymes, and the like. It was experimentally found that the feeding of suckling piglets, three days before weaning from sows, a micellar form of vitamin E at a dose of 4.5 mg per 1 kg of body weight and a double intramuscular injection of a complex of citrates of trace elements at a dose of 2.5 and 30 cm3 per 10 kg of body weight leads to an increase in anabolic processes of protein metabolism, which is confirmed by an increase in the total protein content and albumin and a decrease in the content of urea in the piglets’ blood serum, the actual increase in the content of which indicates an increased level of metabolism and the growth intensity, since albumins are involved in the construction of components cells of muscle tissue, and when studying the total protein content, an increase in its level was found within the physiological norm, which indicates the active growth of young animals.